Analysis of Displacement in Somalia - World Bank Group (Washington, DC, 2014)
Development and humanitarian actors currently engaged in Somalia face the challenge of delivering assistance in such a way that it is supportive of peace and state building, addresses the acute vulnerability, and dependence of large shares of the population while operating in a still insecure and changing environment. Forced displacement is a key feature of the current political economy context of Somalia. The necessity of addressing displacement is partly due to the scale and duration of the phenomenon. Displacement dynamics have fundamentally reshaped Somali culture in multiple ways. The purpose of this study is to inform the Bank and other development and humanitarian actors on the scale, characteristics, and political economy dimensions of displacement in Somalia. The study was undertaken between February and June 2013 by a team from the Tana Copenhagen. The conceptual framework for the study was based on one for political economy assessments. In this context the report presents, introduction; history, causes, and characteristics of displacement in Somalia; current internally displaced person (IDP) situation; prospects for return; vulnerabilities and development needs of the displaced; political economy challenges; and development for IDPs - recommendations.